Remittances and the Dutch Disease: an empirical analysis in the context of Ethiopia - Mohammed Yimam Ali; Getachew Abebaw Ayele (Cogent Social Sciences)
The Dutch Disease, initially associated with natural resource discovery, has evolved to include various capital inflows. This study investigates the relationship between remittance inflows and the Dutch Disease in Ethiopia, focusing on the real effective exchange rate. Using a 30-year time series (1991–2020) and a Vector Error Correction Model, the study finds a robust long-run relationship among remittances, official development assistance, money supply, terms of trade, domestic credit, and real gross domestic product. The empirical results reveal that remittances, along with other variables, significantly affect the real effective exchange rate in both the short and long run. Contrary to the Dutch Disease hypothesis, remittance inflows did not lead to real effective exchange rate appreciation in the long run. Trade liberalization and government consumption of non-tradables were also identified as influential factors. The short-run dynamics indicate a significant speed of adjustment towards equilibrium, emphasizing the importance of understanding the macroeconomic impacts of remittances on real effective exchange rate. Policy implications include managing real effective exchange rate through targeted interventions, considering trade liberalization to enhance export competitiveness, and designing remittance policies to utilize capital for economic development without fearing Dutch Disease consequences. The study also recommends the disaggregation of foreign aid data for more nuanced policy insights. Overall, this research contributes valuable insights for policymakers in navigating the complexities of remittances, economic variables, and the real effective exchange rate in Ethiopia, facilitating informed and effective policy decisions.